Peningkatan Aktivitas dan Hasil Belajar Ekonomi Materi Permasalahan Ketenagakerjaan melalui Penerapan Metode Snowball Throwing pada Siswa SMAN 1 Ciawi - Karyawan, Awan (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
The purpose of this study was to find out the activities and learning outcomes of economics on employment issues through the application of the snowball throwing method to class XI IPS 3 students of SMAN 1 Ciawi in the 2018/2019 academic year. This research was conducted using classroom action research method. This research was conducted at SMA Negeri 1 Ciawi, District Ciawi, the reason the author conducted research at SMA Negeri 1 Ciawi is because the author serves and teaches as a teacher of Economics. using the snowball throwing method learning in class XI IPS 3 SMAN 1 Ciawi, this can be seen from the level of student learning completeness per cycle, namely in the pre-cycle with a KKM of 75 students who completed the pre-cycle there were 11 students or 28.95%, cycle I there are 18 students or 47.37% and in the second cycle there are 34 students or 89.47%. This shows what teachers do to improve learning outcomes by using the snowball throwing method learning successfully and achieving the specified indicator, which is 75%.